Análise do pré-mix de breu esterificado e policloreto de alumínio como agente de colagem interna em sistemas alcalinos - Santos, Ivan Rodrigues dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The papers produced in alkaline systems shows better properties than those produced in acidic systems and enable the use of calcium carbonate as a filler. This research aimed to enable the use of a rosin based product as internal sizing agent in neutral/ alkaline system of papermaking process. Three studies were conducted research for the development of a new sizing agent, the differential being the esterification of rosin then pre-mixing with PAC (polyaluminium chloride) at different concentrations. The sizing agents were evaluated on papers made up of bleached ECF pulp industry, starch, cap and sizing agent. The sheets formed with the additives were evaluated for sizing efficiency (Cobb test, Edge Wickings peroxide, lactic acid and water) in paper coating line of paper card - 100 g/m². It was also conducted a study in industry through laboratory simulation. It's about the application from the sizing agent in the mass of paper machine covering layer #9 Klabin - Monte Alegre Unit. A second study aimed to evaluate the performance of different sequences pulp bleaching kraft-O2 eucalyptus in internal sizing of the surface layer of the paper card. Six different bleaching sequences, being four ECF's - D(E+P)DD; AHTD(E+P)DD; AHTD(E+P)DP; AHTDEDP, an ECF-Light - AHTD(PO)D and a new short bleaching sequence ECF - AHTDP are investigated. The pulps were bleached to 90 ± 0.5% ISO. The pulps were refined in PFI mill and refine the curve was determined by previous tests. The pulps held at 40 ° Schopper-Riegler (° SR). Thereafter, handsheets (100 g / m²) were formed with 10 kg/t industrial sizing agent plus 6 kg/t industrial PAC, at different pH ranges (7.0, 7.5, 8.0). Quality parameters analyzed were Cobb test, Edge Wickings peroxide, lactic acid and water. The results proved the efficiency of the new sizing agent to the parameters evaluated

Os papéis produzidos em sistemas alcalinos apresentam melhores propriedades dos que os produzidos em sistemas ácidos além de possibilitar a utilização de carbonato de cálcio como carga. A presente pesquisa teve como objetivo viabilizar a utilização de breu como agente de colagem interna em meios neutro/alcalinos de produção de papel. Na pesquisa foram realizados três estudos para o desenvolvimento de um novo agente de colagem, sendo o diferencial a esterificação do breu seguida de pré-mixagem com policloreto de alumínio (PAC) em diferentes concentrações. As colas foram avaliadas em papéis formados por polpa industrial branqueada ECF, amido, PAC e cola. As folhas formadas com os aditivos foram avaliadas com relação à eficiência de colagem em linha de cobertura de papel cartão com gramatura de 100 g/m². Também foi realizado um estudo em indústria, através de simulação laboratorial de aplicação na massa da camada de cobertura da máquina de papel da Klabin - Unidade de Monte Alegre. Um segundo estudo teve como objetivo avaliar o desempenho de diferentes sequências de branqueamento de celulose de eucalipto kraft-O2 na colagem interna da camada superficial do cartão de papel. Seis sequências diferentes de branqueamento foram avaliadas, sendo quatro ECF - D(E+P)DD; AHTD(E+P)DD; AHTD(E+P)DP e AHTDEDP - uma ECF-Light - AHTD(PO)D e uma nova sequência ECF - AHTDP. As polpas foram branqueadas para 90 ± 0,5% ISO. Após o branqueamento as polpas foram refinadas até que atingissem 40° Schopper-Riegler (SR°). Depois disso, as folhas (100 g/m²) foram formadas com 10 kg/t de agente de colagem industrial com a adição de 6 kg/t de PAC, em diferentes pH's (7,0;7,5 e 8,0). Os parâmetros de qualidade analisados foram teste de Cobb e Edge Wickings peróxido, lático e água. Os resultados provaram a eficiência da nova cola para os parâmetros avaliados
Pre-mix of esterified rosin and polyaluminum chloride as internal sizing agent in alkaline systems
Keywords: Gomas e resinas; Papel - Confecção - Quimica; Branqueamento; Papermaking Chemistry